A magnesium negative electrode polymer protective layer and its preparation method and application
By coating the halogen-containing polymer protective layer on the surface of the magnesium negative electrode, the problems of passivation of the magnesium negative electrode and electrolyte corrosion are solved, the electrochemical window is broadened and the cycle life of the battery is improved.
Patent Information
- Application Number
- CN202110889806.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-04
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-08-04
AI Technical Summary
Passivation of the surface of the magnesium negative electrode and corrosion problems of the current collector and battery shell caused by the chlorine-containing electrolyte limits the electrochemical window and cycle life of the battery.
Using halogen-containing polymer as a protective layer, coated on the surface of the magnesium negative electrode, and an artificial SEI layer is formed through the adhesion and film-forming properties of the polymer, limiting the diffusion of halogen ions, reducing the magnesium deposition overpotential and improving the reversible magnesium deposition of magnesium deposition. sex.
It effectively prevents direct contact between the negative magnesium electrode and the electrolyte, inhibits side reactions during charging and discharging, reduces the corrosion of halogen ions on the current collector and battery shell, broadens the electrochemical window, and improves the cycle life of the battery.
Smart Images

Figure CN115706209B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium batteries, and in particular to a magnesium negative electrode polymer protective layer and a preparation method and application thereof. Background Art
[0002] In recent years, the energy crisis and environmental crisis have become increasingly severe, which has promoted the rapid development of large-scale energy storage fields such as electric vehicles and energy storage grids. Lithium-ion batteries have been widely used in the field of new energy vehicles due to their high energy density, high operating voltage, long cycle life, low self-discharge rate, no memory effect, fast charging and discharging, and environmental friendliness. At the same time, many problems of lithium-ion batteries, such as poor safety and high prices, have also been slowly exposed. Therefore, finding a non-lithium chemical power source that is highly safe, low-cost, and environmentally friendly has become an important research topic for electrochemists at home and abroad.
[0003] Magnesium is abundant in the earth's crust, about 1,000 times more abundant than lithium. my country's magnesium reserves are 22.5% and rank first in the world. Therefore, the cost of magnesium-ion batteries made from magnesium is much lower than that of lithium-ion batteries. Magnesium ions are in a two-electron valence state. Due to the two-electron characteristics of magnesium metal, its volumetric capacity is as high as 3833mAh / cm 3 , much higher than the 2046mAh / cm of metallic lithium 3 In addition, magnesium metal has low chemical activity and is not prone to dendrites as a negative electrode. It also has a high melting point (922K), which greatly improves the safety of chemical power sources. Therefore, magnesium-ion batteries are considered to be one of the ideal replacement products for lithium-ion batteries in the future.
[0004] In traditional magnesium ion liquid batteries, due to Mg 2+ The potential of magnesium is -2.37 V vs. SHE. Magnesium metal can undergo redox reactions with most common electrolyte components (including solvents and magnesium salts), thereby forming a dense non-conductive Mg on the surface of the magnesium negative electrode. 2+The passivation layer is not conducive to the reversible deposition / dissolution of metallic magnesium. At present, there have been a large number of studies on solving the problem of surface passivation of magnesium negative electrode by improving the electrolyte (Adv. Energy Mater. 2017, 7, 1602055; J. Mater. Chem. A, 2017, 5, 10815), and there are also many studies on solving the interface passivation problem by developing magnesium alloy negative electrodes (Adv. Energy Mater. 2019, 9, 1902086; Angew. Chem. Int. Ed. 2020, 59, 21728–21735), but there are very few studies on directly protecting the surface of magnesium negative electrode. Only Ban achieved reversible deposition / dissolution of magnesium in traditional ester electrolyte by coating a layer of magnesium-conductive polymer on the surface of magnesium powder in 2018. However, this method requires the use of explosive magnesium powder, and the operation is complicated and there are safety issues (Nat. Chem. 2018, 10, 532).
[0005] At present, the commonly used magnesium ion battery electrolytes are mainly Grignard reagent electrolytes, magnesium aluminum chloride complex (MACC) electrolytes and Mg (TFSI) 2-based electrolytes. The coordination structure of magnesium-chloride ions in the above electrolytes plays a very critical role in the normal operation of magnesium batteries, mainly in alleviating the passivation of magnesium negative electrodes, reducing deposition overpotential, enhancing magnesium deposition kinetics and improving magnesium deposition reversibility. However, the presence of chloride ions is a double-edged sword. Since chloride ions in chloride-containing electrolytes can diffuse freely with the electrolyte, the chloride ions diffused everywhere will cause corrosion of the battery collector, electrode and battery shell, limiting the electrochemical window of the battery. This is also a major challenge currently faced by chloride-containing electrolytes. Summary of the invention
[0006] The purpose of the present invention is to solve the problems of passivation of the surface of the magnesium metal negative electrode and corrosion of the current collector and the battery shell by the chlorine-containing electrolyte, and to provide a magnesium negative electrode polymer protective layer and a preparation method and application thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A magnesium negative electrode polymer protective layer, wherein the polymer protective layer is a polymer coated on a magnesium negative electrode active material layer; the polymer is a halogen-containing polymer;
[0009] As mentioned above, the polymer is composed of repeating structural units, and the main chain of the repeating structural unit can be straight chain or with branched chains; wherein any H on the straight chain and / or branched chain in the main chain is substituted.
[0010] At least one H on the main chain of the polymer repeating structural unit is substituted by an -X group or an -R1X group; wherein X is a halogen atom or ion; and R1 is selected from an alkyl group, an alkoxy group, a quaternary ammonium group, an aryl group, an aryloxy group, an alkyl magnesium group or an alkoxy magnesium group, preferably a C1-C6 alkyl group, a C1-C6 alkoxy group, a quaternary ammonium group, an aryl group, an aryloxy group, a C1-C6 alkyl magnesium group or a C1-C6 alkoxy magnesium group, and further preferably a quaternary ammonium group, a C1-C4 alkyl magnesium group or a C1-C4 alkoxy magnesium group.
[0011] The polymer main chain is polyether, polyolefin, polyester, polysiloxane or polyamide, or two or more of the main chains are copolymerized.
[0012] The relative molecular mass of the polymer is 5-5 million.
[0013] Preferably, the main chain of the polymer is polyether, polyolefin or polysiloxane.
[0014] The thickness of the polymer protective layer is 1 nm-1 mm.
[0015] A method for preparing a magnesium negative electrode polymer protective layer comprises dissolving one or more halogen-containing polymers in an organic solvent to form a uniform solution; coating the solution on the surface of a magnesium negative electrode active material layer by scraping, spin coating or spraying; and obtaining a uniform polymer coating after drying.
[0016] One or more of the polymers are dissolved in an organic solvent; wherein the organic solvent is one or a mixture of dichloromethane, chloroform, carbon tetrachloride, toluene, dimethyl sulfoxide, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or acetone, preferably one or a mixture of dichloromethane, N-methylpyrrolidone or acetonitrile.
[0017] An application of a magnesium negative electrode polymer protective layer, and an application of the magnesium negative electrode polymer protective layer in the preparation of a magnesium-based battery.
[0018] The magnesium-based battery is a primary magnesium battery or a secondary magnesium battery.
[0019] A magnesium negative electrode with a polymer protective layer, wherein the magnesium negative electrode contains the polymer protective layer.
[0020] The magnesium negative electrode is a polymer protective layer coated on the surface of the active material layer; wherein the active material of the magnesium negative electrode active material layer is one or more of pure magnesium foil, pure magnesium sheet, magnesium alloy sheet, pure magnesium powder and magnesium alloy powder.
[0021] Principle of the invention: The present invention applies a halogen-containing polymer as a protective film on the surface of the negative electrode active material. Since the polymer has good adhesion and film-forming properties, it can be evenly and densely covered on the surface of the negative electrode active material to form a layer of artificial SEI, delaying the passivation of the magnesium negative electrode. At the same time, the introduction of halogens into the polymer can, on the one hand, reduce the magnesium deposition overpotential, enhance the magnesium deposition kinetics and improve the reversibility of magnesium deposition. On the other hand, compared with the traditional liquid chlorine-containing electrolyte, the halogen is confined to the negative electrode surface, avoiding the corrosion of the current collector and the battery shell caused by the free diffusion of the halogen, thereby broadening the electrochemical window.
[0022] The beneficial effects of the present invention are:
[0023] The magnesium negative electrode with a polymer protective layer of the present invention has a simple preparation method. The polymer protective layer prevents direct contact between the magnesium negative electrode and the electrolyte, and inhibits side reactions during the charge and discharge process. In addition, the polymer protective layer limits the halogen ions on the surface of the magnesium negative electrode, reduces the corrosion of the halogen ions on the current collector and the battery shell, and broadens the electrochemical window of the battery. At the same time, the halogen ions in the polymer protective layer can also regulate the solvation structure of the magnesium ions at the negative electrode interface, reduce the deposition overpotential, and improve the reversibility of magnesium deposition, thereby improving the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 a is a photograph of the magnesium negative electrode after polymer protection provided in Embodiment 1 of the present invention;
[0025] Figure 1 b is a scanning electron microscope photograph of the surface of the magnesium negative electrode after polymer protection provided in Example 1 of the present invention;
[0026] Figure 1 c is a scanning electron microscope photograph of the cross section of the magnesium negative electrode after polymer protection provided in Example 1 of the present invention;
[0027] Figure 1 d is a scanning electron microscope photograph of the cross section of the magnesium negative electrode after polymer protection provided in Example 1 of the present invention;
[0028] Figure 2 This is the long cycle polarization curve of the Mg / Mg symmetric battery before and after polymer protection provided in Example 1 of the present invention;
[0029] Figure 3 This is the electrochemical window test result of magnesium on stainless steel battery before and after protection provided by Example 2 of the present invention;
[0030] Figure 4 This is the electrochemical window test result of magnesium on stainless steel battery before and after protection provided by Example 3 of the present invention;
[0031] Figure 5a is an electron microscope photograph of the magnesium negative electrode after cycling of the unprotected Mg / Mg symmetric battery provided in Example 5 of the present invention;
[0032] Figure 5 b is an electron microscope photograph of the magnesium negative electrode of the unprotected Mg / Mg symmetric battery after cycling provided in Example 5 of the present invention;
[0033] Figure 5 c is an electron microscope photograph of the magnesium negative electrode after the protection of the Mg / Mg symmetric battery after cycling provided in Example 5 of the present invention;
[0034] Figure 5 d is an electron microscope photograph of the magnesium negative electrode after the protection of the Mg / Mg symmetric battery after cycling provided in Example 5 of the present invention;
[0035] Figure 6 This is the long cycle polarization curve of the Mg / Mg symmetric battery after polymer protection provided in Example 6 of the present invention. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below through specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] In a glove box filled with argon, polymer A (see Formula 1) was dissolved in anhydrous dichloromethane to prepare a 1% solution for use. Then, the magnesium sheet was polished with sandpaper in the glove box to remove the oxide layer on the surface, and was punched into a disc with a diameter of 14 mm. The prepared solution was then spin-coated on the magnesium sheet with the oxide layer removed, and after drying, a magnesium negative electrode protected by polymer A was obtained (see Figure 1 ad). Figure 1 As shown in a, it can be seen that a layer of polymer is evenly coated on the surface of the magnesium sheet. By observing the surface scanning electron microscope image of the magnesium sheet after protection ( Figure 1 b) It was found that the protective layer was very smooth and evenly covered the surface of the magnesium sheet. Figure 1 The thickness of the polymer protective layer measured by scanning electron microscopy cross-sectional image in d is 6 μm.
[0039] Where n is 1000
[0040] Using 0.5 mol / L Mg(TFSI)2 / DME as electrolyte and glass fiber as separator, a symmetrical battery was assembled using the protected magnesium sheet as the negative electrode in a glove box filled with argon. At the same time, a symmetrical battery was assembled using the unprotected magnesium sheet as the negative electrode for comparison. The two assembled batteries were tested at 0.5 mA / cm2 The charge and discharge cycles are carried out at a current density of , and the long cycle curve is as follows Figure 2 The results show that the polarization voltage of the unprotected Mg / Mg symmetric battery is about 2V, and it fails after 20 cycles, while the polarization voltage of the protected Mg / Mg symmetric battery is only about 0.15V, and it can be stably cycled for more than 50 cycles, greatly extending the battery life.
[0041] Example 2
[0042] In a glove box filled with argon, polymer A (see formula 1) was dissolved in anhydrous dichloromethane to prepare a solution with a mass fraction of 1% for use. Then, the magnesium sheet was polished with sandpaper in the glove box to remove the oxide layer on the surface, and was punched into a disc with a diameter of 14 mm. The prepared solution was then spin-coated on the magnesium sheet with the oxide layer removed, and after drying, a magnesium negative electrode protected by polymer A was obtained.
[0043] The battery was assembled in an argon-filled glove box using 0.5mol / L Mg(HMDS)2 / DME as the electrolyte and glass fiber as the separator. The battery was assembled using protected magnesium sheets as the negative electrode and stainless steel sheets. The electrochemical window of the battery was tested using an electrochemical workstation with a linear scan at a rate of 0.1mV / s. The control group was assembled using a liquid chlorine-containing electrolyte (0.5mol / L Mg(HMDS)2+0.5mol / LMgCl2) and unprotected magnesium sheets and steel sheets, and the electrochemical window was tested in the same way (see Figure 3 ).like Figure 3 As shown, the electrochemical window of the protected battery can reach 3.4V, while the electrochemical window of the unprotected battery is only 2.2V.
[0044] Example 3
[0045] In a glove box filled with argon, polymer B (see formula 2) was dissolved in anhydrous N-methylpyrrolidone to prepare a solution with a mass fraction of 1% for use. Then, the magnesium sheet was polished with sandpaper in the glove box to remove the oxide layer on the surface, and was punched into a disc with a diameter of 14 mm. The prepared solution was then spin-coated on the magnesium sheet and stainless steel sheet with the oxide layer removed, and after drying, a magnesium negative electrode and a stainless steel positive electrode protected by polymer B were obtained.
[0046] Where n is 2000
[0047] The battery was assembled in an argon-filled glove box using 0.5 mol / L Mg(TFSI)2 / DME as the electrolyte and glass fiber as the separator. The battery was assembled using the protected magnesium sheet as the negative electrode and the stainless steel sheet. The electrochemical window of the battery was tested by linear scanning at a speed of 0.1 mV / s using an electrochemical workstation. The control group used an unprotected magnesium sheet and steel sheet to assemble the battery, and the electrochemical window was tested in the same way (see Figure 4 ).like Figure 4 As shown, the electrochemical window of the protected battery can reach 3.5V, while the electrochemical window of the unprotected battery is 2.4V.
[0048] Example 4
[0049] In a glove box filled with argon, polymer C (see formula 3) was dissolved in anhydrous N-methylpyrrolidone to prepare a solution with a mass fraction of 1% for use. Then, the magnesium sheet was polished with sandpaper in the glove box to remove the oxide layer on the surface and punched into a disc with a diameter of 14 mm. The prepared solution was then spin-coated on the magnesium sheet and stainless steel sheet with the oxide layer removed, and after drying, the magnesium negative electrode and stainless steel positive electrode protected by polymer C were obtained. With 0.5 mol / L Mg(TFSI)2 / DME as the electrolyte and glass fiber as the diaphragm, the battery was assembled with the protected magnesium sheet as the negative electrode and the stainless steel sheet in a glove box filled with argon. The electrochemical window of the battery was tested by linear scanning at a speed of 0.1 mV / s using an electrochemical workstation. The electrochemical window of the protected battery can reach 3.4V, which is much higher than the 2.4V of the unprotected battery.
[0050] Where n is 2000
[0051] Example 5
[0052] In a glove box filled with argon, polymer D (see formula 4) was dissolved in anhydrous dichloromethane to prepare a solution with a mass fraction of 1% for use. Then, the magnesium sheet was polished with sandpaper in the glove box to remove the oxide layer on the surface, and was punched into a disc with a diameter of 14 mm. The prepared solution was then spin-coated on the magnesium sheet with the oxide layer removed, and after drying, a magnesium negative electrode protected by polymer D was obtained.
[0053] Where n is 1000
[0054] Using 0.5mol / L Mg(TFSI)2 / DME as electrolyte and glass fiber as separator, a symmetrical battery was assembled in a glove box filled with argon using the protected magnesium sheet as the negative electrode. At the same time, a symmetrical battery was assembled using the unprotected magnesium sheet as the negative electrode for comparison. The two assembled batteries were tested at 0.5mA / cm 2 The battery was disassembled after 10 cycles and the morphology of the magnesium negative electrode was observed using a scanning electron microscope (see Figure 5 ).Depend on Figure 5 It was found that the deposition of magnesium was more uniform after protection, while there was more uneven deposition on the surface of the unprotected magnesium negative electrode.
[0055] Example 6
[0056] In a glove box filled with argon, polymer E (see formula 5) was dissolved in anhydrous dichloromethane to prepare a solution with a mass fraction of 1% for use. Then, the magnesium sheet was polished with sandpaper in the glove box to remove the oxide layer on the surface, and punched into a disc with a diameter of 14 mm. The prepared solution was then spin-coated on the magnesium sheet with the oxide layer removed, and after drying, a magnesium negative electrode protected by polymer E was obtained.
[0057] Where m is 100 and n is 50
[0058] Using 0.5mol / L Mg(TFSI)2 / DME as electrolyte and glass fiber as separator, a symmetrical battery was assembled in a glove box filled with argon using the protected magnesium sheet as the negative electrode. At the same time, a symmetrical battery was assembled using the unprotected magnesium sheet as the negative electrode for comparison. The two assembled batteries were tested at 0.5mA / cm 2 The charge and discharge cycles were carried out at a current density of 2.5 Å. The results showed that the polarization voltage of the unprotected Mg / Mg symmetric battery was around 2 V and it failed after 20 cycles ( Figure 2 a), while the polarization voltage of the protected Mg / Mg symmetric battery is only about 0.16V, and it can be stably cycled for more than 100 cycles ( Figure 6 ), the battery life is greatly extended.
Claims
1. A magnesium negative electrode polymer protective layer, characterized in that: The polymer protective layer is a polymer coated on the magnesium negative electrode active material layer; The polymer is Where n is 1000; Where n is 2000; Where n is 2000; Where n is 1000; Where m is 100 and n is 50.
2. A method for preparing the magnesium negative electrode polymer protective layer according to claim 1, characterized in that: One or more polymers are dissolved in an organic solvent to form a uniform solution; the solution is coated on the surface of the magnesium negative electrode active material layer; and a uniform polymer coating is obtained after drying.
3. The method for preparing the magnesium negative electrode polymer protective layer according to claim 2, characterized in that: One or more of the polymers are dissolved in an organic solvent; wherein the organic solvent is one or a mixture of dichloromethane, chloroform, carbon tetrachloride, toluene, dimethyl sulfoxide, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or acetone.
4. An application of the magnesium negative electrode polymer protective layer according to claim 1, characterized in that: Application of the magnesium negative electrode polymer protective layer in the preparation of magnesium-based batteries.
5. A magnesium negative electrode having a polymer protective layer, characterized in that: The magnesium negative electrode comprises the polymer protective layer according to claim 1.
Citation Information
Patent Citations
Metal negative electrode and preparation method thereof, electrochemical battery and terminal
CN112447943A